Optimizing Public Health: Socialization of Comprehensive Self-Medication for Hypertension Through Traditional Medicine in Community of Kedon, Rejosari Village, Bandongan District, Magelang Regency - Soraya, Devinta Febri; Abdillah, Salma Iliyina; Widiyanto, Andi; Rizal, Mar'ie Muhammad; Yulina, Rayung Putri; Lina (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
Self-medication is an effort to self-medicate, the implementation of which involves recognizing the symptoms of a disease and selecting the medication on one's own initiative without going to a doctor or other health worker. Hypertension is a health problem that is quite dangerous throughout the world because hypertension is the main risk factor that leads to cardiovascular disease such as heart attack, heart failure, stroke and kidney disease. Alternative medicine or preventative measures are conventional medicine. The use of traditional medicine, especially plants, to improve public health is increasingly widespread. The use of medicinal plants, either alone or in combination, has long been used to reduce the symptoms of high blood pressure. Medicinal plants that are known to lower blood pressure include celery leaves and cat's whisker leaves. Both plants contain compounds that can help prevent high blood pressure. The aim of this activity is to increase public awareness of the importance of maintaining normal blood pressure and to find out the effect of giving traditional plant preparations which can be used as antihypertensives on the blood pressure of residents of RT 3 Bandongan District who experience hypertension.